Transposon insertion mapping with PIMMS, Pragmatic Insertional Mutation Mapping System - Blanchard, Adam M.; Leigh, James A.; Egan, Sharon A.; Emes, Richard D. (Frontiers, 2015)
The PIMMS (Pragmatic Insertional Mutation Mapping System) pipeline has beendeveloped for simple conditionally essential genome discovery experiments in bacteria.Capable of using raw sequence data files alongside a FASTA sequence of thereference genome and GFF file, PIMMS will generate a tabulated output of each codingsequence with corresponding mapped insertions accompanied with normalized resultsenabling streamlined analysis. This allows for a quick assay of the genome to identifyconditionally essential genes on a standar d desktop computer prioritizing results forfurther investigation.